DINAMIKA SPIRITUALITAS ISLAM: KAJIAN HISTORIS DAN SOSIOKULTURAL ATAS TAREKAT SERTA PERKEMBANGANNYA DALAM MASYARAKAT MUSLIM NUSANTARA - Abdul Wahab Syakhrani; Ahmad Ghazali; Rahman (Adisam Publisher, 2026)
This study discusses the dynamics of Islamic spirituality through historical and sociocultural studies of Sufi orders and their development in Muslim communities in the Indonesian archipelago. Sufi orders, as spiritual institutions in the Sufi tradition, play an important role in shaping the religious, social and cultural dimensions of Muslim communities in various regions. Through a historical approach and social analysis, this study traces the process of dissemination, adaptation, and transformation of Sufi teachings that occurred in conjunction with interactions with local cultures and changes over time. The results of the study show that Sufism not only functions as a vehicle for spiritual guidance, but also as a social and moral network that influences the religious structure, education, and cultural dynamics of Muslim communities in the Indonesian archipelago from classical times to the modern era.